Digitalisasi Layanan Posbakum: Studi Kebutuhan dan Model Konseptual Chatbot “SI-SATSET” Sebagai Penguatan Akses Keadilan - Neni Rakhmawati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The development of digital technology has driven transformations in public services, including the judicial sector. Legal Aid Posts (Posbakum) in Religious Courts play a strategic role in ensuring access to justice, particularly for vulnerable and economically disadvantaged communities. Although Posbakum services have been implemented in accordance with Supreme Court Regulation (PERMA) Number 1 of 2014, challenges persist at the pre-litigation stage, especially regarding the public’s initial legal information readiness and administrative preparedness. Field data from the Posbakum of the Slawi Religious Court for the period January-August 2025 show that out of 1,337 registered cases, approximately 600 applicants arrived with administratively incomplete documents at their initial visit. These shortcomings were generally technical and could be completed within the same service flow. This condition indicates the need to strengthen access to early legal information that is clear, understandable, and easily accessible. This study aims to analyze community needs for digital-based Posbakum services at the pre-litigation stage and to formulate a conceptual chatbot model as an alternative service enhancement. The research employs a descriptive qualitative approach through interviews, observations, and document analysis. The findings indicate that the community requires a legal information system that is simple, interactive, and accessible via mobile devices. Based on these findings, this study proposes the SI-SATSET chatbot model (Simple, Accountable, Targeted, Efficient, and Affordable Information System) as a digital pre-litigation assistant. This model is expected to support Posbakum performance, strengthen community legal empowerment, and improve access to justice in Religious Courts.